Quality of Business, Entrepreneurship Education and Business Start-up Intentions among Students in Serbia: Research Results - Ćoćkalo, Dragan Živko; Đorđević, Dejan; Bogetić, Srđan; Sajfert, Dragana; Minovski, Robert (Industrija, 2013)
This paper will present findings of a research conducted among students in the Republic of Serbia dealing with quality of business, entrepreneurship and business start-ups. Throughout a three year period the research has included 1990 examinees. The population is built on students from four universities and business schools directed towards business and management. The research has been conducted using a structured questionnaire. Among other, the research has shown that a number of examinees were not informed of the existence of financial incentives for starting a business. Interviewed students reported that they lack the knowledge of: the basics of entrepreneurship and small business, basic finance and accounting and foreign languages. In the opinion of students, the Republic of Serbia is currently no suitable environment that encourages youth to start their own businesses. The results of this research point out the fact that the state must have the key role in this sphere of Serbian market through a creation of certain documents whose aim is promoting the concept of the young as entrepreneurs. A research of this scope has so far not been conducted on the territory of the Republic of Serbia, and to the best of the authors’ knowledge not even in the West Balkans region.